GRIT AND ACADEMIC SELF-EFFICACY AS PREDICTORS OF SENIOR HIGH SCHOOL ACADEMIC PERFORMANCE - Mata, Purity V (Journal of Agriculture and Technology Management; Vol 23 No 1 (2020): Vol 23 No 1 (2020): Journal of Agriculture and Technology Management (JATM) Volume 23 January - June 2020 Issue, 2020)
It is widely accepted that intelligent individuals are more likely to succeed compared to academically challenged individuals. Knowledge is, without a doubt, a powerful tool. But interestingly, for long term goals, it should be sealed with perseverance and passion, which is termed as grit, a non-cognitive trait. This study assessed the academic performance, grit and academic self-efficacy of 303 senior high school students in North District Carmen, Cebu using standardized scales. For data analysis, Pearson’s correlation coefficient and multiple regression analysis were utilized as statistical tools. The results revealed that students’ academic performance is rated as proficient with m = 86.86, SD = 3.31. Students’ grit score has a m = 3.40, SD = 0.29, which indicates an above-average level of grit. In terms of academic self-efficacy, students have a mean of 4.00, SD = 0.46, indicating an above-average level of academic self-efficacy. Furthermore, a significant positive correlation among students’ academic performance, grit, and academic self-efficacy was found with statistical significance at the level .01. It is concluded that an increase in grit and academic self-efficacy scores lead to an increase in academic performance. Finally, multiple regression analysis shows that students' grit and academic self-efficacy are statistically significant predictors of academic success, accounting for 12.3% of the variance in academic performance.